Numerical Study Of Aerodynamic Performance Of Hatchback Vehicle Fitted With A Strip Spoiler: Effect Of Yaw Angle - Cheng, See Yuan; Abdullah, Mohd Azman; Zakaria, Mohamad Shukri; Mansor, Shuhaimi (Penerbit Akademia Baru, 2018)
This study investigated the effect of yaw angle on the aerodynamic performance of hatchback vehicle model fitted with a strip spoiler. Conventionally, the performance of rear-roof spoilers had mainly been optimized for straight-ahead driving condition. However, during cornering, the effect of spoiler is most needed to ensure that the vehicle can drive through the curve without slip. Hence, this study aims to investigate the effects of yaw angle change corresponding to cornering on the flow characteristics of strip spoiler, and the subsequent influence on the aerodynamic performance of hatchback vehicles. A RANS-based computational fluid dynamics (CFD) method was used. A simplified hatchback model was adopted. The numerically obtained results was compared to the experimental data for validation of the CFD method.It was found that both the lift and drag coefficient of the spoiler were to increase with increasing yaw angle. Similarly, the overall Cd and Cl of the model were also increased with increasing yaw angle. The main body parts that contributed to the increase in Cd are the base and slant, whereas the front tended to attenuate the Cd. Meanwhile, the rise in Cl was mainly caused by the roof, and resisted by the underbody.